Exploring the Pathways to Digital Education: The Roles of Satisfaction with Learning and Impulsive Behavior as Predictors of Openness and Attitude towards Digital Applications - Alexandru-Filip Popovici; Georgeta Pânișoară; Cristina Marina Ghiță; Denisa Berceanu (Babes-Bolyai University, 2023)
The present research aims to investigate the impact of satisfaction with learning, risk-taking behavior, impulsive buying behavior, attitudes, and openness toward adopting new applications, on 296 respondents. The study's results allows the significant highlighting of the relationship between satisfaction with learning and attitudes toward digital applications. Individuals exhibiting higher satisfaction with their learning experiences tended to display a slightly more favourable attitude towards adopting applications. Linear regression analyses revealed significant predictive factors, underscoring the influence of individual characteristics on attitudes and openness towards applications. Of particular importance were impulsive behaviour and satisfaction with learning, which emerged as consistent predictors, emphasizing the role of personal traits and experiences in shaping perceptions of digital applications. The findings contribute to the existing body of knowledge and hold implications for educational strategies, consumer behaviour, and technology adoption.